(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This paper presents a comprehensive assessment of power quality in an industrial refrigeration and freezing facility based on a continuous monitoring campaign, analyzing voltage, current, harmonic distortion, voltage unbalance, flicker severity, power flow characteristics, and load behavior in order to evaluate the influence of electrical supply conditions on the operational reliability, energy performance, and stability of refrigeration equipment under real operating conditions. The results demonstrate that all monitored power quality indicators remained within the limits prescribed by applicable standards, confirming the suitability of continuous power quality monitoring as an effective tool for ensuring reliable and uninterrupted operation of industrial refrigeration systems.